The Patterns of Utilization of Interscalene Nerve Blocks for Total Shoulder Arthroplasty. (September 2016) - Gabriel, Rodney A.; Nagrebetsky, Alexander; Kaye, Alan D.; Dutton, Richard P.; Urman, Richard D.
Abstract : The interscalene block (ISB) is a common adjunct to general anesthesia for total shoulder arthroplasty (TSA). The aim of the study was to report the current national demographics of the patients who are receiving ISB for TSAs. We performed a retrospective analysis of data from the National Anesthesia Clinical Outcomes Registry from 2010 to 2015. Of 28, 810 cases, 42.1% received an ISB. Only 0.83% of cases received regional anesthesia as the primary anesthetic. From 2010 to 2014, there has been an increase in ISB utilization for this surgery (odds ratio, 1.21; 95% confidence interval, 1.19–1.23; P < .0001). Furthermore, we report a geographic distribution of block utilization in the United States. We have identified national patterns for the utilization of regional anesthesia for TSAs that may provide insight into future design of research studies.